Original paperComparison of learning strategies in successful and unsuccessful students - Fathi-Ashtiani, Ali; Hasani, Maryam; Nabipoor-Ashrafi, S. Mahdi; Ejei, Javad; Azadfallah, Parviz (Archives of Medical Science, 2007)
Introduction: The main purpose of the present research was to compare learning strategies used by successful and unsuccessful students. Material and methods: Six hundred and five third-year students were randomly selected from all-girl high schools in Tehran based on their level of academic achievement. The students were enrolled in one of three groups: the Mathematics group (which included Math and Physics), the Experimental Sciences group (Biology and Chemistry), or the Humanities Group (Sociology and History). The very highest and lowest achieving students in each of these groups were compared (using t-tests and discriminant analysis) for their use of four learning strategies: Rehearsal, Elaboration, Organization, and Comprehension Monitoring. Results: In each of the three groups, there were significant differences between the successful and unsuccessful students in the use of learning strategies. In all three groups, high achieving students relied more than low achieving students on Comprehension Monitoring, but there was no difference in the use of Rehearsal. There was a difference between groups in the use of Elaboration or Organization. In the Mathematics and the Humanities groups, high achieving students relied more than low achieving students on Elaboration, whereas in the Experimental Sciences group, high achieving students relied more on Organization. Moreover, discriminant analysis showed that the use of Elaboration by students in the Mathematics and Humanities groups and Comprehension Monitoring by students in the Experimental Science group contributed most to educational achievement. Conclusions: Learning strategies make a difference for academic achievement. Therefore, we must familiarize ourselves with a variety of learning strategies, learn them and teach them to our students, and we should attempt to change the idea that students can discover strategies by themselves in order to help our children grow to their fullest potential and prosper.